Adolescents’ Career Decision Making: A Qualitative Study - Asghar, Sameen; Ajmal, Muhammad Asir (Pakistan Journal of Humanities and Social Sciences, 2022)
The purpose of this study was to investigate the factors influencing career decision making of adolescents at higher secondary level of education. A qualitative inquiry was done using grounded theory method that aimed at developing a career decisions theory which is indigenous to Pakistani culture and society. Sample consisted of adolescents studying at higher secondary level of education in different schools and colleges of Lahore, Pakistan. Semi structured interview schedule was used to collect the data. Telephonic interviews were conducted. A combination of purposive, snowball and convenience sampling strategies was employed for data collection. A total fifty interviews were conducted and based upon the richness of the data provided; fourteen interviews were selected for further analysis. The results show that ‘’scope’’, family influences, influence of institution, peer influences, planning, gender, knowledge about ones’ self, beliefs, need for change, finances, command on subject matter, looking towards future, market value, international and local system of education and preconceived notions about fields are the factors that influence career decisions of adolescents in Pakistan. Implications in both basic and applied areas of research were discussed.